The Influence of Governance Characteristics and Enterprise Risk Management on Intellectual Capital in Banking in Indonesia - Rohayati, Rohayati; Hady, Hamdy; Nalurita, Febria (Gema Wiralodra, 2024)
Intellectual capital (IC) is a crucial driver of developing knowledge-based economic value for an organization, such as a bank. With intellectual capital, company can generate knowledge-based economic value as a source of competitive advantage, influencing innovation and value for stakeholders. This research aims to analyze and explain the influence of governance characteristics and enterprise risk management on intellectual capital in banking in Indonesia. The independent variables are audit committee, board independence, institutional ownership, enterprise risk management, return on assets, leverage and corporate social responsibility as well as the dependent variable intellectual capital. The data used in this research is secondary data sourced from the annual reports of banking companies listed on the Indonesia Stock Exchange (BEI) during the period 2018 to 2022. The research sample was selected using a purposive sampling method so that 42 companies were sampled. The data analysis used to test the hypothesis is multiple regression analysis using e-views 9. The research results show that the audit committee has a positive effect, board independence has a negative effect, institutional ownership has a negative effect, enterprise risk management has no effect, return on assets has an effect positively, leverage has no effect, and corporate social responsibility has a negative effect on intellectual capital. Implications of this research to understand how bank managers affect intellectual capital, this study examines a variety of factors, including audit committee, board independence, institutional ownership, enterprise risk management, return on assets, leverage and corporate social responsibility. It suggests that managers should focus on enhancing their intellectual capital to make informed investment decisions and effectively manage their bank's resources, thereby enhancing their investment performance.